Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1001/jama.279.13.1036-jms0401-4-1
|View full text |Cite
|
Sign up to set email alerts
|

The Geriatrics Imperative: Meeting the Need for Physicians Trained in Geriatric Medicine

Abstract: Pulse is prepared by the Pulse editors and JAMA staff and is published monthly from September through May. It provides a forum for the ideas, opinions, and news that affect medical students and showcases student writing, research, and artwork. The articles and viewpoints in Pulse are not necessarily the policy of the AMA or JAMA. All submissions must be the original unpublished work of the author. Work submitted to Pulse is subject to review and editing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…2 The number of physicians trained and certified as geriatricians is not likely to meet this growing demand, and physician assistants (PAs), along with primary care physicians and nurse practitioners, will be increasingly expected to care for elderly patients. [3][4][5][6][7][8][9] The needs of this aging population and the potential for PAs to help meet this need have been cited for more than 20 years. 10 However, very few PAs work primarily in geriatrics and this appears not to have changed over the last 2 decades.…”
Section: Introductionmentioning
confidence: 99%
“…2 The number of physicians trained and certified as geriatricians is not likely to meet this growing demand, and physician assistants (PAs), along with primary care physicians and nurse practitioners, will be increasingly expected to care for elderly patients. [3][4][5][6][7][8][9] The needs of this aging population and the potential for PAs to help meet this need have been cited for more than 20 years. 10 However, very few PAs work primarily in geriatrics and this appears not to have changed over the last 2 decades.…”
Section: Introductionmentioning
confidence: 99%
“…O ur philosophy at the University of Texas Health Science Center at San Antonio is that all medical students need to be prepared to care for the large numbers of aging patients they will see in their practices. 1 Simultaneously, the faculty strives to nurture a select group of students interested in careers in geriatrics, both clinical and academic. 2 A new course required for all first-year medical students provides the foundation for this effort by helping students become more comfortable interacting with older people and dispelling stereotypes about aging.…”
mentioning
confidence: 99%
“…Although Thailand's growth rate of its aging population is three times faster than that of the developed countries, there is no data surveying the attitude of both MS and MR trainees toward geriatric medicine that would help steer the direction of curricular development (''World population prospects: The 2006 revision population database, '' 2007). Previous studies suggested that most medical students have little knowledge about aging, have mixed attitudes about the elderly and their care, and have low interest in pursuing geriatric medicine as a career (Chiang, 1998;Coccaro & Miles, 1984). Additionally, one study showed that only 4% of doctors who chose geriatric medicine as a career in the United Kingdom made their career choice while they were medical students (Briggs, Atkins, Playfer, & Corrado, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Care for the elderly requires specific knowledge, attitudes, and skills that expand across the continuum of medical education from medical school through postgraduate training. Previous studies showed that medical students have mixed attitude towards the elderly and their care and low interest to pursue a career in geriatric medicine (Chiang, 1998;Coccaro & Miles, 1984). Additionally, there was a study that reported an association between students' positive attitudes about the elderly and their care and an increased interest in geriatric medicine (Fitzgerald, Wray, Halter, Willians, & Supiano, 2003).…”
mentioning
confidence: 99%